Human Performance in the Nuclear Industry - Koncz, Steven M. (Nuclear Science and Technology, 2015)
Management of employees human performance in the Nuclear Industry is endemic to their safety when working. In the United Kingdom it has been a key focus since 2003. Employees were made aware through a detailed program of workshops, of the error prevention methods and how to apply them. The use of effective incident barriers became embedded in the safety culture. The methodology implemented was personal ownership, to enable self assessment of behaviors, attitudes and beliefs. When put in place, there are many specific barriers, which can reduce the chances of an error occurring. They come under the headings of organisational, procedural and physical barriers. All of these were used in some way and continue to be reinforced on a daily basis. Specific barriers are applied in specific situations. However, some general ones are also effective. In common use are the Take 2 or Take 5 Minutes, point of work risk assessments. Applying the human performance barrier Independent Verification (I.V.) would result in ’Take 3 and I.V.’ This would independently double check the risk assessment. New ways of thinking are required to continuously improve and evolve. Results of the error reduction process included; reduced workload, increased plant reliability, efficiencies and productivity.